2012
DOI: 10.1590/s1517-86922012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Resposta da frequência cardíaca durante sessão de treinamento de karatê

Abstract: Karate practice can promote beneficial adaptations on the health-related components of physical fitness. Among the components, the maximum oxygen uptake ( O 2max ) is an important indicator of cardiorespiratory fitness, as it is also a strong and independent predictor of the risk of death from cardiovascular disease and all other causes. Previous studies have evaluated the heart rate (HR) responses in the karate modality during protocols elaborated by researchers who simulated training. However, the results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(42 reference statements)
1
2
0
4
Order By: Relevance
“…This could ensure better training program results. Notably, the correlation observed in the present study supports results observed in other studies [34][35][36]38,39 . Our study, therefore, adds important information to existing literature, specifically regarding FT monitoring.…”
Section: Discussionsupporting
confidence: 93%
“…This could ensure better training program results. Notably, the correlation observed in the present study supports results observed in other studies [34][35][36]38,39 . Our study, therefore, adds important information to existing literature, specifically regarding FT monitoring.…”
Section: Discussionsupporting
confidence: 93%
“…Although most of the time had occurred between 60% and 90% of HRmáx, the karate athletes remained predominantly below the intensity correspondent to the ventilatory threshold. However, it is important to note that the thresholds in this study [64] were observed in high percentages of HRmax (83-90%) %), and caution should be taken when considering that karate athletes train mostly below the ventilatory threshold.…”
mentioning
confidence: 75%
“…Posteriorly, Milanez et al [64] also evaluated the HR response during a karate training session (n = 9). After the determination of the variables related to the treadmill maximal incremental test (VO2, %HR, %HR ventilatory threshold and respiratory compensation point -RCP), the athletes were submitted to a typical karate training session (shorter effort periods with duration of 2-min; basic techniques, combined techniques and combined techniques against opponent; small intervals of 30s and 60s were used to change techniques or resting).…”
mentioning
confidence: 99%
“…Ao longo das últimas décadas, a prática de artes marciais tem se difundido em todo o mundo e, também, no Brasil [1][2][3][4] 21 Rev Bras Med Esporte 2012 Jiu-jitsu M Artioli et al 6 Rev Bras Med Esporte 2006 Judô M Artioli et al 7 Rev Nutr 2007 Judô M Artioli et al 8 Rev Bras Educ Fís Esporte 2011 Judô M Barreira e Massimi 9 Psicol Reflex Crit 2008 Karatê ---Barros et al 22 Rev Bras Med Esporte 2010 Judô M/F Barsottini et al 10 Rev Bras Med Esporte 2006 Judô M/F Dias et al 11 Motriz 2011 Judô M/F Fabrini et al 23 Rev Bras Educ Fis Esporte 2010 Judô M Castro Júnior 24 Rev Bras Cienc Esporte 2004 Capoeira M Lima et al 12 Rev Bras Med Esporte 2004 Judô M Martins et al 25 Rev Bras Geriatr Gerontol 2013 Karatê ---Massa et al 13 Rev Bras Educ Fis Esporte 2011 Judô M Mendes et al 14 Rev Bras Med Esporte 2009 Judô M Milanez et al 26 Rev Bras Med Esporte 2012 Karatê M/F Milanez et al 27 Rev Bras Med Esporte 2012 Karatê M/F Nunes et al 15 Rev Bras Med Esporte 1998 Judô M Pereira et al 16 Motriz 2010 Judô F Pinto Neto 28 Rev Bras Ensino Fis 2006 Kung-Fu M Souza et al 17 Rev Bras Med Esporte 2011 Karatê / Jiu-jitsu M Tamborindeguy et al 29 Rev Bras Cienc Esporte 2011 Taekowndo M Vieira et al 19 J Epilepsy Clin Neurophysiol 2007 Judô ---Yoshitomi et al 20 Rev Bras Med Esporte 2006 Judô M * M= Masculino; F= Feminino Além disso, a ausência de estudos relacionados aos benefícios da prática de artes marciais para a saúde é uma limitação importante, pois, cresce cada vez mais a busca da população por uma melhor qualidade de vida por meio da atividade física 31 . As artes marciais poderiam assim ser uma opção a mais para a população.…”
Section: Introductionunclassified